2013
DOI: 10.1039/c3ta12587d
|View full text |Cite
|
Sign up to set email alerts
|

Hollow polylactic acid microcapsules fabricated by gas/oil/water and bubble template methods

Abstract: Hollow capsules are gas-filled spherical particles. Hollow biodegradable capsules with a diameter of a few microns are expected to be used as diagnostic ultrasound contrast agents and carriers of drug-delivery systems, while those with a diameter of a few tens of microns have been widely used in various engineering applications and medical and pharmaceutical applications, providing weight reduction of the material and improved thermal and acoustical insulation. In this study, uniformly sized hollow polylactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…As described previously, the release of H2 bubbles during the reduction of Se powder could influence the subsequent precipitation of Cu2Se, as they can prevent the aggregation of nanoparticles. [59][60][61] Prolonging the reduction time of the Se powder may reduce their influence [ Figure 5(a)]. We therefore investigated the effect of reduction time on the particle size of the Cu2Se precipitates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, the release of H2 bubbles during the reduction of Se powder could influence the subsequent precipitation of Cu2Se, as they can prevent the aggregation of nanoparticles. [59][60][61] Prolonging the reduction time of the Se powder may reduce their influence [ Figure 5(a)]. We therefore investigated the effect of reduction time on the particle size of the Cu2Se precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…ΔG (PbTe) > ΔG (PbSe), and the deviation demonstrates that the formation of nanostructured metal chalcogenides is not only dominated by their formation energy (or extremely low Ksp), but also could be related to other reaction parameters such as the release of H2 bubbles (Figure 1), which could play the role of surfactant during formation of nanostructures. [58][59][60][61] During the preparation of metal tellurides, the reduction of Te powder usually lasted longer (around 5 hours in Table S2) than the reduction of selenium powder (30 min). The slow release of H2 bubbles leads to less bubbles during precipitation and cannot effectively prevent the growth of nanoparticles, resulting in bigger particles than in their selenide analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Soft templates encompass bacteria, 9 surfactant micelles, 10 emulsions, 11,12 vesicles, 13,14 and so on, 15 while the dimensional instability and polydispersion of soft templates restrict the fine regulation of microcapsule structures. Soft templates encompass bacteria, 9 surfactant micelles, 10 emulsions, 11,12 vesicles, 13,14 and so on, 15 while the dimensional instability and polydispersion of soft templates restrict the fine regulation of microcapsule structures.…”
Section: Introductionmentioning
confidence: 99%
“…In general, templates can be divided into hard templates and soft templates. Soft templates encompass bacteria, 9 surfactant micelles, 10 emulsions, 11,12 vesicles, 13,14 and so on, 15 while the dimensional instability and polydispersion of soft templates restrict the fine regulation of microcapsule structures. Hard templates encompass SiO 2 , 16,17 CaCO 3 , [18][19][20] polystyrene spheres, 21,22 and so on, and the well-defined morphology and stable/controllable size of hard templates can effectively manipulate the microcapsule structures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to the best of our understanding, none of the previous studies have considered that bubble nucleation during the drying process of a polymer solution is the result of the supersaturation of a gas already dissolved in the solution. This is the basis of our proposed method for the fabrication of hollow polymeric microcapsules by encapsulating microbubbles, that is, the bubble template method. However, our research group recently found that the presence of polymers not only aids the stabilization of the nucleated bubbles inside the droplet but also affects the solubility of the gas in the solution. Gas sorption in polymers is well known, and this phenomenon can be described by the Flory–Huggins equation, yet the effect of the polymer on the solubility of gases in polymer solutions requires further study.…”
Section: Introductionmentioning
confidence: 99%